Almost one year of COVID-19 pandemic: how radiotherapy centers have counteracted its impact on cancer treatment in Lombardy, Italy. CODRAL/AIRO-L study. Issue 2 (April 2022) - Jereczek-Fossa, Barbara Alicja; Palazzi, Mauro Filippo; Tonoli, Sandro; Zaffaroni, Mattia; Marvaso, Giulia; Ivaldi, Giovanni Battista; Amadori, Marcello; Antognoni, Paolo; Arcangeli, Stefano; Buffoli, Alberto; Beltramo, Giancarlo; Bignardi, Mario; et al.
Lombardy has represented the Italian and European epicenter of the coronavirus disease 2019 (COVID-19) pandemic. Although most clinical efforts within hospitals were diverted towards the care of virally infected patients, therapies for patients with cancer, including radiotherapy (RT), have continued. During both the first and second pandemic waves, several national and regional organizations provided Italian and Lombardian RT departments with detailed guidelines aimed at ensuring safe treatments during the pandemic. The spread of infection among patients and personnel was limited by adopting strict measures, including triage procedures, interpersonal distance, and adequate implementation of personal protective equipment (PPE). Screening procedures addressed to both the healthcare workforce and patients, such as periodic nasopharyngeal swabs, have allowed the early identification of asymptomatic or pauci-symptomatic COVID-19 cases, thus reducing the spread of the infection. Prevention of infection was deemed of paramount importance to protect both patients and personnel and to ensure the availability of a minimum number of staff members to maintain clinical activity. The choice of treating COVID-19–positive patients has represented a matter of debate, and the risk of oncologic progression has been weighted against the risk of infection of personnel and other patients. Such risk was minimized by creating dedicated paths, reserving time slots, applying intensified cleaning procedures, and supplying personnel and staff with appropriate PPE. Remote working of research staff, medical physicists, and, in some cases, radiation oncologists has prevented overcrowding of shared spaces, reducing infection spread.